Development High Thermal Conductivity Tool Steel on Hot Press Forming: An Overview - Zulhishamuddin, A. R.; S. N., Aqida (2014)
Thermal conductivity properties in die material are very important in hot press forming (HPF) processes. High composition of thermal conductivity in die material can contribute to high cooling rate, which is indirectly can produce fully martensitic in microstructure that would change the blank properties into high hardness and strength, up to 1500 MPa. Powder metallurgy method has been used to produce high conductive steel with homogenous carbide distribution with less segregation and porosity. Thus, die defect such as thermal fatigue can be reduced and help to extend the die’s life. There are other methods that are being used to produce new die materials properties, like cast alloy with new composition, direct metal deposited (DMD), selective laser melting (SLM), direct metal laser sintering (DMLT) and spray forming. Among of the factors that contribute to increase the thermal conductivity in steel is the composition of metal in that steel itself. Elements like manganese (Mn), nickel (Ni), molybdenum (Mo), tungsten (W) and chromium (Cr) can increase the thermal conductivity by producing carbide network. The carbide network can increase the thermal conductivity among the microstructure in the steel. Thermochemical software was used to simulate and model phase diagram and thermodynamic properties for new materials. Currently the higher thermal conductivity can reached up to 66 W/mk has been produce by powder metal from Rovalma, Spain. To develop high thermal conductivity tool steel, casting with carbide former composition can help to enhanced thermal conductivity tool steel since it feasible and cheaper. While it is the best way to produce cooling cannel within die on hot press forming.